5
$\begingroup$

$$\lim_{x\to 0} {\ln(\cos x)\over \sin^2x} = ?$$

I can solve this by using L'Hopital's rule but how would I do this without this?

$\endgroup$

closed as off-topic by heropup, Mike Haskel, Henrik, Brevan Ellefsen, Leucippus Aug 16 '16 at 3:08

This question appears to be off-topic. The users who voted to close gave this specific reason:

  • "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – heropup, Mike Haskel, Henrik, Brevan Ellefsen, Leucippus
If this question can be reworded to fit the rules in the help center, please edit the question.

  • 2
    $\begingroup$ Do you know Taylor expansions? If yes, use them! $\endgroup$ – paf Aug 15 '16 at 16:46
  • $\begingroup$ I know expansions of cosx , sinx , ln(1+x)...but how to use them here? $\endgroup$ – Sujan Dutta Aug 15 '16 at 16:56
  • $\begingroup$ See my edit below $\endgroup$ – paf Aug 15 '16 at 17:03
  • 1
    $\begingroup$ Basically, there are many many ways to do it :P $\endgroup$ – Patrick Stevens Aug 15 '16 at 17:06
  • $\begingroup$ @PatrickStevens The best and worst parts of Calculus in a nutshell. $\endgroup$ – Simply Beautiful Art Aug 15 '16 at 21:48
11
$\begingroup$

$$\frac{\log\left(\cos\left(x\right)\right)}{\sin^{2}\left(x\right)}=\frac{1}{2}\frac{\log\left(1-\sin^{2}\left(x\right)\right)}{\sin^{2}\left(x\right)}=-\frac{\sin^{2}\left(x\right)+O\left(\sin^{4}\left(x\right)\right) }{2\sin^{2}\left(x\right)}\stackrel{x\rightarrow0}{\rightarrow}-\frac{1}{2}.$$

$\endgroup$
  • $\begingroup$ I was looking for this type of answer. $\endgroup$ – Sujan Dutta Aug 15 '16 at 16:54
7
$\begingroup$

The expression equals

$$\frac{\ln (\cos x) - \ln (\cos 0)}{\cos x - \cos 0}\cdot\frac{\cos x - 1}{x^2}\cdot \frac{x^2}{\sin^2 x}.$$

The first fraction $\to \ln'(1) = 1,$ by definition of the derivative. The limit of the second fraction is standard and equals $-1/2.$ The third fraction $\to 1.$ So the limit is $-1/2.$

$\endgroup$
6
$\begingroup$

You can use the important limits: $\lim_{x\rightarrow 0}\frac{\sin x}{x} =1$ and $\lim_{x\rightarrow 0}(1+x)^{\frac{1}{x}}=e$ (i.e., $\lim_{x\rightarrow 0} \frac{\ln(1+x)}{x}=1$). Then \begin{align*} \lim_{x\rightarrow 0}\frac{\ln \cos x}{\sin^2 x} &= \lim_{x\rightarrow 0}\frac{\cos x -1}{x^2}\\ &=\lim_{x\rightarrow 0}\frac{-2\sin^2 \frac{x}{2}}{x^2}\\ &=-\frac{1}{2}. \end{align*}

$\endgroup$
  • 1
    $\begingroup$ Need $\neq$ can. But yes, this is the simplest approach (although the OP may not be familiar with the notations. $\endgroup$ – Clement C. Aug 15 '16 at 16:53
6
$\begingroup$

In THIS ANSWER, I showed using only the limit definition of the exponential function and Bernoulli's Inequality that the logarithm function satisfies the inequalities

$$\frac{x-1}{x}\le \log(x)\le x-1 \tag 1$$

for $x>0$.

Then, we have from $(1)$

$$\frac{\cos(x)-1}{\cos(x)\sin^2(x)}\le \frac{\log(\cos(x))}{\sin^2(x)}\le \frac{\cos(x)-1}{\sin^2(x)} \tag 2$$

Now, using the trigonometric identity $\cos(x)-1=-2\sin^2(x/2)$ in $(2)$ reveals

$$-2\frac{\sin^2(x/2)}{\cos(x)\sin^2(x)}\le \frac{\log(\cos(x))}{\sin^2(x)}\le -2\frac{\sin^2(x/2)}{\sin^2(x)} \tag 3$$

whereby application of the squeeze theorem to $(3)$ gives the coveted limit

$$\lim_{x\to 0}\frac{\log(\cos(x))}{\sin^2(x)}=-\frac12$$

Note that we used the result $\log_{x\to 0}\frac{\sin(x)}{x}=1$, which can be obtained a number of ways including using the well-known inequalities from elementary geometry

$$x\cos(x)\le \sin(x)\le x$$

for $|x|\le \pi/2$.

$\endgroup$
4
$\begingroup$

Note that $$\lim_{x\to 0}\frac{1-\cos x}{x^2}=\lim_{x\to 0}\frac{2\sin^2(\frac x2)}{x^2}=\lim_{x\to 0}\frac 14 \frac{2\sin^2(\frac x2)}{\frac{x^2}{4}}=\frac{1}{2}$$ Now, $$\lim_{u\to 1}\frac{\ln u}{u-1}=\ln'(1)=1$$ Hence, since $u=\cos x$ tends to 1 when $x$ tends to 0: $$\lim_{x\to 0}\frac{\ln(\cos x)}{\cos x-1}=1$$ So $$\lim_{x\to 0}\frac{\ln(\cos x)}{x^2} =\lim_{x\to 0}\frac{\ln(\cos x)}{\cos x-1}\lim_{x\to 0}\frac{\cos x-1}{x^2}=-\frac{1}{2}$$

Finally, since $$\lim_{x\to 0} \left(\frac{\sin x}{x}\right)^2 = 1^2=1$$ ,we have $$\lim_{x\to 0}\frac{\ln(\cos x)}{\sin^2x}=\lim_{x\to 0}\frac{\ln(\cos x)}{x^2}\lim_{x\to 0} \left(\frac{x}{\sin x}\right)^2=-\frac{1}{2}$$

Edit: with Taylor expansions, life becomes easier! Near 0, we have $$\frac{\ln(\cos x)}{\sin^2x}=\frac{\ln\left(1-\frac{x^2}{2}+o(x^2)\right)}{x^2+o(x^2)}$$

Since $\ln(1+u)=u+o(u)$ near 0, we obtain (letting $u=-\frac{x^2}{2}+o(x^2)$ above): $$\frac{\ln(\cos x)}{\sin^2x}=\frac{-\frac{x^2}{2}+o(x^2)}{x^2+o(x^2)}$$ near 0. So the limit is $-\frac 12$.

$\endgroup$
3
$\begingroup$

This way doesn't require fiddling with Taylor series or interchanging any sums and limits; it's an example of one of the many places where we can simplify things by recognising a derivative.

Substituting $u = \cos(x)$, we obtain $$\lim_{u \to 1} \frac{\log u}{1-u^2} = \lim_{u \to 1} \left[ \frac{\log u}{1-u} \times \frac{1}{1+u} \right]$$

Now, this is just $$\frac{1}{2} \times \lim_{u \to 1} \frac{\log(u)}{1-u} = -\frac{1}{2} \lim_{h \to 0} \frac{\log(1+h) - \log(1)}{h}$$ where we have substituted $h=-(1-u)$ and introduced the term $\log(1) = 0$ in the numerator.

That final limit is just $\frac{d}{dx} \log(x)$ evaluated at $x=1$; i.e. $1$.


Strictly speaking, I suppose what we should do is find the limit when approached from above, and then the limit when approached from below, and show that they are the same. Otherwise the $u=\cos(x)$ substitution isn't obviously kosher. The calculations will be exactly the same.

$\endgroup$
2
$\begingroup$

$$\frac{\log\left(\cos\left(x\right)\right)}{\sin^{2}\left(x\right)}=\frac{\log\left(1+\cos\left(x\right) -1 \right)}{\sin^{2}\left(x\right)}$$ $$\lim_{x\to 0} \frac{\log\left(1+\cos\left(x\right) -1 \right)}{\sin^{2}\left(x\right)}.\frac{x^2}{x^2}.\frac{\left(\cos\left(x\right) -1 \right)}{\left(\cos\left(x\right) -1 \right)}$$

$\endgroup$
  • $\begingroup$ Hm, this answer feels somewhere between incomplete and a duplicate of zhw's answer. $\endgroup$ – Simply Beautiful Art Aug 15 '16 at 21:55
  • $\begingroup$ @SimpleArt What is incomplete ? $\endgroup$ – Aakash Kumar Aug 16 '16 at 1:05
  • $\begingroup$ It is simply not as enlightening as zhw's answer and requires too much effort figuring out how to arrange the terms to get the right form for a good limit. (at least in my opinion, but I didn't downvote simply because of this) $\endgroup$ – Simply Beautiful Art Aug 16 '16 at 1:08
  • $\begingroup$ @SimpleArt I don't think it require too much effort , especially to those who are good at limit .The whole question can be easily solved in two steps . $\endgroup$ – Aakash Kumar Aug 16 '16 at 3:38
1
$\begingroup$

We can solve this problem by using our knowledge of limits for composite functions.

Let $u = \sin^2 x.$

$x \to 0 \implies \sin^2 x \to 0 \implies u \to 0$

$\frac{\ln (\cos x)}{\sin^2x} = \frac{\ln (\cos^2 x)}{2\sin^2x} = \frac{\ln (1 - \sin^2 x)}{2\sin^2x} = \frac{\ln (1 - u)}{2u} = 1/2 \ln(1-u)^\frac{1}{u}$

Note that $\ln(1-u)^\frac{1}{u}$ is continuous at u = 0 and is equal to $1/e$, so we use the limit rule for composite functions to get

$\lim_{x \to 0} \frac{\ln (\cos x)}{\sin^2 x} = \frac{1}{2} \lim_{u \to 0}\ln(1-u)^\frac{1}{u} = \frac{1}{2}\ln \frac{1}{e} = -\frac{1}{2}$

$\endgroup$

Not the answer you're looking for? Browse other questions tagged or ask your own question.